Uma teoria sobre tolerância: o conceito de tolerância na formação dialética da subjetividade - Porto, Larissa Cristine Gondim (Universidade Federal de São Carlos, 2019)
A theory about toleration must deal with the difficulties of its practice. As a concept that is built around moral and political grounds, toleration can be described as necessary and useful, or even offensive and redundant. The hypothesis argued in this thesis is that it is necessary to restructure the concept of toleration, because there is a narrow link between theories of toleration and specific notions of subjectivity, in a way that it is possible to reformulate the concept of toleration by changing the underlying definition of subjectivity that it endorses. Using a dialectical methodology, and taking inspiration from the structure of Hegelian dialectic, it is proposed that there are three main overlapping figures in which toleration can be described. The first figure, called subjective toleration, is based on the individualism thesis and defines toleration as a negative act of putting up with something that causes aversion. This classical discourse of toleration is constantly linked to the development of political liberalism, but leads to paradoxes that refute it. Because of these paradoxes, a second figure of intersubjective toleration arises. Grounded in the Hegelian phenomenology and its contemporary interpretations, the road to self consciousness leads to the development of an idea of toleration as the restriction of desire, within the act of recognition. Thus, toleration turns into recognition, because both can be described as a process of double negative, in which desire of one selfconscious is reciprocally restrained towards the other selfconcious. The paradox of this figure lies in the fact that there is no normative ground that imposes this recognition as a duty. To fulfill this gap, it is necessary a third figure, the objective toleration, based on a democratic thesis, which defines toleration as an element of the bildung of political subjectivity through social and ethical liberty. Then, toleration becomes a way to critique political neutrality, and must be incorporated in institutions of direct and indirect power, as a tool to inclusiveness in difference. Through the dialectical movement of these three figures, it is possible to observe how toleration sublates into a more general and inclusive perspective and becomes an intrinsic part of the contemporary moral and political subjectivity.
A theory of tolerance: the concept of toleration in the dialectical bildung of subjectivity
Keywords: Tolerância; Reconhecimento; Autoconsciência; Toleration; Recognition; Selfconsciousness; CIENCIAS HUMANAS::FILOSOFIA::ETICA